Zdzisław Beksiński i ponowoczesna melancholia. Zarys interpretacyjny (Na końcu ogrodu, Centrala snów, Informator) - Szczyrek, Paweł (Tematy i Konteksty, 2019)
The artistic output of Zdzisław Beksiński finds recognition all over the world. Not so long ago, his visual heritage was enriched by new, literary accomplishments – the collection of short stories written by the artist between 1963 and 1965. The present paper is an analysis of three most expressive pieces in terms of studied esthetics: Na końcu ogrodu, Centrala snów oraz Informator. Beksiński’s short stories are here placed in the context of postmodern melancholy characterized by affirmation of experienced emptiness the source of which was sought for in Beksinski’s generational experiences. On these grounds, a thesis is proposed where the holistic creative concept which merges visual and literary accomplishments is expressed by three figures: decay, repetition and ontological uncertainty. Not only is the object of the analysisa theoretical aspect of a worldview present in the literary works but it also functions as a specific fictional-structural solution.